FEATURES OF MORPHOLOGY AND CHEMICAL COMPOSITION OF NATIVE GOLD FROM THE MURTYKTY DEPOSIT, SOUTH URALS - N.S. Chukhareva; E.V. Belogub; Yu.A. Ryzhkova; I.A. Blinov; M.A. Rassomakhin; K.A. Novoselov (Минералогия)
The morphology and chemical composition of native gold from the Murtykty deposit (South Urals) are discussed in the paper. Native gold is subdivided into five types: 1) inclusions in sulfides, 2) grains in fractures and interstices of pyrite and other sulfides, 3) grains at the boundaries of sulfides and gangue minerals, 4) inclusions in gangue minerals and their interstices and 5) «free╗ grains from heavy concentrates. The chemical composition of 128 gold grains is studied. In accordance with Ag content (from 6.49 to 30.8 wt. %), native gold from the deposit varies from high- to low-fineness (rare grains). Native gold in sphalerite contains Cu (0.85–2.27 wt. %)., The morphological features of 264 gold grains are quantified using Image Tool software. The morphological characteristics of native gold from types 1–4 are similar. The data on morphology and size of native gold grains can be used for improvement of technology of gold extraction.